Psychological resources as predictors of academic performance of first-year students in higher education - Kotzé, Martina; Niemann, Rita (University of the Free State, 2013)
This article aims to determine whether psychological resources (hope, optimism and resilience) can be potential predictors of academic performance. A cross-sectional survey design was used and the sample consisted of 789 first-year students in Industrial Psychology. The measuring instruments included the State Hope Scale (SHS), the Life Orientation Test-Revised (LOT-R), and the Adult Resilience Indicator (ARI). The results of the simple multiple regression analysis showed that state hope, and specifically pathways, and three dimensions of resilience were statistically significantly related to academic performance, whereas optimism was not a statistically significant predictor of academic performance

Die doel van die artikel is om te bepaal of die positiewe sielkundige hulpbronne (hoop, optimisme en veerkragtigheid) potensiële voorspellers van akademiese prestasie kan wees. ’n Dwarssnitontwerp is gebruik in die uitvoering van die studie. Die steekproef het 789 eerstejaarstudente in Bedryfsielkunde ingesluit en die State Hope Scale (SHS), Life Orientation Test-Revised (LOT-R) en die Adult Resilience Indicator (ARI) is as meetinstrumente gebruik. Die resultate van die eenvoudige meervoudige regressie-analise het getoon dat daar statisties-beduidende korrelasies tussen hoop, spesifiek die subskaal, alternatiewe roetes tot doelwitbereiking (‘pathways’) en akademiese prestasie bestaan het, asook tussen drie dimensies van veerkragtigheid en akademiese prestasie. Optimisme was nie ’n voorspeller van akademiese prestasie nie.
Keywords: First-year students; Higher education; Academic achievement